FAO fisheries circular N.866: Feed ingredients for crustaceans natural foods and processed feedstuffs - Albert G J. Tacon (FAO, 1993)
The paper reviews the natural feeding habits of decapod crustaceans and the major natural foods and processed feed ingredients used within compound aquafeeds for crustaceans, including fish and fishery by-product meals, terrestrial animal by-product meals, single cell proteins, aquatic plants, oilseeds and by-product meals, grain legumes and by-product meals, cereal grains and by-product meals and miscellaneous plant products. Information is also presented concerning the nutritional value of individual feed ingredient sources, together with their normal dietary inclusion levels. In addition, the document presents information on world crustacean aquaculture production and highlights the current trends and future prospects of feed ingredient usage within crustacean aquafeeds.